No Benefit from Omega-3 Supplements in Addition to Optimal Medical Therapy - Vinall, Maria (MD Conference Express, 2009)
Results from the OMEGA [NCT00251134] trial showed that dietary supplementation with omega-3 fatty acids offers no additional benefits when added to optimal medical therapy in patients who have suffered a heart attack.